2007
DOI: 10.1037/0022-006x.75.4.605
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting the type of tactics used to resist sexual assault: A prospective study of college women.

Abstract: The purpose of the current study was to examine how women's intentions, as well as psychological and situational factors, predicted the actual use of resistance tactics in response to a sexual assault situation over a 2-month follow-up period. Twenty-eight percent of the 378 undergraduate women who participated at the baseline assessment and returned for the follow-up session 8 weeks later were victimized over the interim period. The results suggested that women's reported use of verbally assertive tactics was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 47 publications
(83 reference statements)
7
85
0
1
Order By: Relevance
“…The degree of resistance is an important factor for the way the victim and others perceive the sexual assault . Our study shows that almost half the women did not resist, either physically or verbally, during the assault.…”
Section: Discussionmentioning
confidence: 63%
“…The degree of resistance is an important factor for the way the victim and others perceive the sexual assault . Our study shows that almost half the women did not resist, either physically or verbally, during the assault.…”
Section: Discussionmentioning
confidence: 63%
“…Significant predictors of diplomatic BRTTs were increased self-consciousness and feelings of sadness, accounting for 25% of the variance. Other studies utilizing this model or related constructs have found that high relationship expectancies were predictive of both diplomatic and non-forceful BRTTs (Macy, et al 2006;Turchik, et al 2007).…”
Section: Interactions Of Factorsmentioning
confidence: 87%
“…Other research has found that when participants perceive greater negative consequences, such as embarrassment, for not undertaking self-protective behaviors, they are more likely to take action to protect themselves (Orchowski, Untied, & Gidycz, 2012). Interpersonal factors are less well researched but have been associated with specific BRTTs; higher relationship expectancies, relationship concerns, and a prior relationship with the perpetrator have been associated with diplomatic and non-forceful BRTTs (Macy, Nurius, & Norris, 2006;Turchik, et al 2007).…”
Section: Intra-and Interpersonal Factors Less Research Has Examinedmentioning
confidence: 99%
“…Sexual assault is especially prevalent on college campuses (Humphrey & White, 2000). Over a relatively short 10-week academic quarter, between 11% to 28% of college women report some form of unwanted sexual experience, ranging from unwanted sexual contact to rape (Gidycz, Orchowski, King, & Rich, 2008; Rich, Gidycz, Warkentin, Loh, & Weiland, 2005; Turchik, Probst, Chau, Nigoff, & Gidycz, 2007). …”
mentioning
confidence: 99%